Effects of Long-term Exposure to Black Carbon Particles on Growth and Gas Exchange Rates of Fagus crenata, Castanopsis sieboldii, Larix kaempferi and Cryptomeria japonica Seedlings - Masahiro Yamaguchi; Yoko Otani; Kenta Takeda; I. Wuled Lenggoro; Atsushi Ishida; Kenichi Yazaki; Kyotaro Noguchi; Hiroyuki Sase; Naoto Murao; Satoshi Nakaba; Kenichi Yamane; Katsushi Kuroda; et al. (Asian Journal of Atmospheric Environment, 2012)
To clarify the effects of black carbon (BC) particles on growth and gas exchange rates of Asian forest tree species, the seedlings of Fagus crenata, Castanopsis sieboldii, Larix kaempferi and Cryptomeria japonica were exposed to BC particles with sub-micron size for two growing seasons from 1 June 2009 to 11 November 2010. The BC particles deposited after the exposure to BC were observed on the foliar surface of the 4 tree species. At the end of the experiment, the amount of BC accumulated on the foliar surface after the exposure to BC aerosols were 0.13, 0.69, 0.32 and 0.58 mg C m-2 total leaf area in F. crenata, C. sieboldii, L. kaempferi and C. japonica seedlings, respectively. In August 2010, the exposure to BC particles did not significantly affect net photosynthetic rate under any light intensity, stomatal diffusive conductance to water vapour (gs), stomatal limitation of photosynthesis, response of gs to increase in vapour pressure deficit and leaf temperature under light saturated condition in the leaves or needles of the seedlings. These results suggest that the BC particles deposited on the foliar surface did not reduce net photosynthesis by shading, did not increase leaf temperature by absorption of irradiation light, and did not induce plugging of stomata in the leaves or needles of the seedlings. There were no significant effects of BC particles on the increments of plant height and stem base diameter during the experimental period and the whole-plant dry mass at the end of the experiment. These results indicate that the exposure to BC particles with sub-micron size for two growing seasons did not significantly affect the growth and leaf or needle gas exchange rates of F. crenata, C. sieboldii, L. kaempferi and C. japonica seedlings.